2023
DOI: 10.3390/jfb14050262
|View full text |Cite
|
Sign up to set email alerts
|

Collarless Polished Tapered Stems of Identical Shape Provide Differing Outcomes for Stainless Steel and Cobalt Chrome: A Biomechanical Study

Abstract: Cemented polished tapered femoral stems (PTS) made of cobalt–chrome alloy (CoCr) are a known risk factor for periprosthetic fracture (PPF). The mechanical differences between CoCr-PTS and stainless-steel (SUS) PTS were investigated. CoCr stems having the same shape and surface roughness as the SUS Exeter® stem were manufactured and dynamic loading tests were performed on three each. Stem subsidence and the compressive force at the bone–cement interface were recorded. Tantalum balls were injected into the cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent biomechanical study has shown that CoCr PTS stems generate an axial compressive force over three times greater than stainless steel PTS stems of identical geometry, and that they subside significantly more within their cement mantles. 39 This increased motion may explain the increased PFF rate seen with this particular stem brand and material in registry studies. 17,25 This is further backed up by biomechanical studies which confirm that the CPT stem has the lowest torque to fracture compared to other commonly cemented stem types.…”
Section: Pts Stemsmentioning
confidence: 93%
“…A recent biomechanical study has shown that CoCr PTS stems generate an axial compressive force over three times greater than stainless steel PTS stems of identical geometry, and that they subside significantly more within their cement mantles. 39 This increased motion may explain the increased PFF rate seen with this particular stem brand and material in registry studies. 17,25 This is further backed up by biomechanical studies which confirm that the CPT stem has the lowest torque to fracture compared to other commonly cemented stem types.…”
Section: Pts Stemsmentioning
confidence: 93%
“…This Special Issue comprises a total of 22 articles, covering a wide range of interventional medical devices in the cardiovascular and orthopedic fields. The research presented in this Special Issue covers various applications of polymer biomaterials, metal biomaterials, organic biomaterials, and composite biomimetic materials [ 1 , 2 , 3 , 4 , 5 , 6 ]. The primary focus of this Special Issue is to investigate the biomechanical properties of cardiovascular/skeletal materials and devices, reflecting current research interests.…”
mentioning
confidence: 99%